Efficacy and Tolerance of Vascular Electrical Stimulation Therapy in the Management of Vaso-Occlusive Crises in Patients with Sickle Cell Disease: A Phase II Single-Centre Randomized Study in Ivory Coast - Renée-Paule Botti; Sie Saïda Bokoum; Etienne L’Hermite; Dohoma Alexis Silue; Boidy Kouakou; Sarah Anastasie Bognini; Serge Arnaud Agoua; Edgar Mandeng Ma Linwa; Roméo Ayemou; Kouassi Gustave Koffi (Advances in Hematology)
Background. Vaso-occlusive crisis (VOC) is the primary cause of hospitalization in patients with sickle cell disease. Treatment mainly consists of intravenous morphine or nonsteroidal anti-inflammatory drugs (NSAIDs), which have many dose-related side effects. The question arises as to whether vascular electrical stimulation therapy (VEST) could be effective or not on VOCs. Objective. To measure the effectiveness and safety of VEST in reducing the median time spent in severe VOC. Methods. We conducted a phase II, single blinded, randomized, controlled, triple-arm, comparative trial. We included thirty (30) adult patients with severe vaso-occlusive crisis. The study arms were divided as follows: our control group (group 0) constituted of 10 patients followed with conventional therapy (Analgesics + Hydration + NSAIDs), while 20 patients were divided equally into two interventional arms—10 patients followed with VEST + Analgesics + Hydration (group 1) and the other 10 patients followed with VEST + Analgesics + Hydration + NSAIDs (group 2). The primary efficacy endpoint was median time to severe crisis elimination. The secondary end points were median time to end-of-crisis, median tramadol consumption, progress of the haemoglobin level over 3 days, side effects, and treatment failure. Results. The age ranged from 14 to 37 years, including 23 women. We noted a beneficial influence of the VEST on the median time to severe crisis (VAS greater than 2) elimination; 17 hours (group 1) against 3.5 hours (group 2) p=0.0166 and 4 hours (group 3) with p value = 0.0448. Similar significant results were obtained on the diminution of total duration of the crisis (VAS over 0) and median tramadol consumption in patients in the interventional arms. Conclusion. These statistically significant results in the interventional arms suggest that VEST could be an alternative treatment of VOC in sickle cell patients.